CULTIVATING ISLAMIC EDUCATIONAL VALUES IN STREET CHILDREN THROUGH THE RUMAH DEDIKASI INDONESIA (KRDI) COMMUNITY IN MAKASSAR - Ruhaya, Besse; Idris, Syarifuddin; Darussalam, Andi Baso; Muhaimin, Muhammad (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study examines the instillation of Islamic educational values ​​by the Indonesian Dedication House Community (KRDI) among street children in Makassar City. The main focus of this study is the form of instillation, the methods used, and the obstacles faced by the community in implementing non-formal education programs for street children. This study uses a qualitative approach with descriptive and phenomenological methods. Primary data were obtained from the General Chairperson of KRDI, mentors, volunteer teachers, and street children, while secondary data consisted of documents and reports related to KRDI activities. Data collection techniques were carried out through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions with validity tests using data triangulation. The results of the study indicate that KRDI plays a strategic role in fostering street children through religious education, character education, and the development of interests and talents. Obstacles that arise include limited teaching staff, the diverse character backgrounds of street children, and lack of support from parents. The implications of this study highlight that Islamic value-based education models can serve as alternative solutions for non-formal education among marginalized urban groups.